Literature Review on Turnover Intention and Employee Characteristics in Startup Companies - Dila Fina Alyura; Ninik Setiyowati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Turnover intention refers to an employee's tendency or desire to quit or change jobs voluntarily without coercion. Many startups struggle to retain employees long-term, primarily due to the often demanding nature of their work, the uncertainty surrounding the company's direction, and a lack of career clarity. This study employed a systematic literature review, an approach to identifying, reviewing, interpreting, and evaluating all relevant research on the topic under study. This involves defining appropriate research questions and systematically reviewing and identifying journals based on predetermined steps. The results indicate that companies need an integrated approach to addressing turnover intention, particularly among millennial employees. Identifying factors such as compensation, incivility, work quality, mental health, and reward systems, as well as how employee characteristics influence responses to these factors, is an important initial step. It can be concluded that several factors significantly influence employee turnover intention, including workplace incivility, compensation, quality of work life, mental health, and the company's reward system. Each of these factors is interrelated and can strengthen or weaken an employee's desire to remain with the company.